Preoperative testing for low- and intermediate-risk non-cardiac elective surgeries: a systematic review and cost-effectiveness analysis - Meregildo-Rodriguez, Edinson Dante (2021)
Preoperative tests are very common in daily clinical practice. However, ordering preoperative tests is not generally based on the best scientific evidence. When preoperative tests are ordered without justification, they may generate false-positive results, cause to repeat or order new tests and consultations, prolong hospital stay, result in problems to the patient (more risks, confusion and anxiety), and increase costs. A systematic review and cost-effectiveness analysis of preoperative tests for the most frequent low- and intermediate-risk non-cardiac elective surgeries performed at the Hospital Regional Lambayeque were conducted. According to the cost-effectiveness analysis, the annual cost of unnecessary preoperative tests amounts to S/ 62,778.00. However, if preoperative tests were adequately ordered and NICE guidelines were followed, their cost would decrease in 38.34 % (i.e., S/ 138.40 for each patient). The results show that preoperative tests should not be ordered for low- and intermediate-risk non-cardiac elective surgeries on a routinely basis. A thorough preoperative medical evaluation would safely decrease the need of other tests for this type of surgery.